CURRENCY RISK ASSESSMENT OF JOINT-STOCK COMPANIES (International Congress on Economics, Management and Business Studies, 2026)
This paper examines the approaches used to assess currency (exchange-rate) risk faced by joint-stock companies (JSCs). It classifies the principal forms of currency exposure — transaction, translation, and economic — and reviews the main quantitative techniques applied to measure them, with particular emphasis on the exposure-elasticity approach and the Value-at-Risk (VaR) framework. The growing relevance of currency risk assessment for JSCs operating in emerging markets, especially under Uzbekistan's floating exchange-rate regime, is discussed, and practical recommendations for improving measurement and management are proposed.
Keywords: Currency risk, exchange rate, joint-stock company, Value-at-Risk, currency exposure, hedging, emerging markets, financial risk management.